Comprehensive study of power valve system / Mohamad Adli Idris, Nor Azmi Ismail and Shamsul Bahri Shamsuddin - Idris, Mohamad Adli; Ismail, Nor Azmi; Shamsuddin, Shamsul Bahri (Faculty of Mechanical Engineering, 2003)
As we know, 2-strokes engine has a fault that is the incomplete expulsion of exhaust gases and the partial expulsion of the fresh air-fuel mixture with the exhaust gas. This fault has been improved by a research that results in developing the power valve system. One of the main companies that have developed this system is Yamaha.